2019
DOI: 10.1021/acsomega.8b03627
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of the Aggregates of Gemtuzumab Ozogamicin

Abstract: The preparation of antibody drug conjugates (ADCs), particularly those containing hydrophobic payloads, may promote aggregate formation. The aggregate (high molecular mass species, HMMS) is an impurity that must be controlled in the final drug substance and drug product formulation to meet product safety and efficacy. Although there are numerous methods designed to mitigate protein aggregation, some of the reasons for the formation of aggregates in ADCs are unique and specific to the synthetic preparation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…24 Further was shown that greater labeling of the mAb can result in higher tendencies to form aggregates. 36,37 Structural changes upon bioconjugation of polyethylene glycol (PEG), which is a commonly used linker system for ADCs, have been reported to reduce susceptibility by proteases by reduced conformational accessibility, when conjugated to lysine residues. A labeling of 6.8% of all lysine residues was sufficient to reduce trypsin digestion and even further mediated a higher resistance against pepsin and chymotrypsin digestion at a labeling degree of 14% compared to the mAb.…”
Section: Structurementioning
confidence: 99%
“…24 Further was shown that greater labeling of the mAb can result in higher tendencies to form aggregates. 36,37 Structural changes upon bioconjugation of polyethylene glycol (PEG), which is a commonly used linker system for ADCs, have been reported to reduce susceptibility by proteases by reduced conformational accessibility, when conjugated to lysine residues. A labeling of 6.8% of all lysine residues was sufficient to reduce trypsin digestion and even further mediated a higher resistance against pepsin and chymotrypsin digestion at a labeling degree of 14% compared to the mAb.…”
Section: Structurementioning
confidence: 99%
“…2 Such heterogenicity was further studied by its developer with size-exclusion chromatography – the species with higher average drug loading were found to be responsible for forming aggregates. 55 Physical instability such as aggregation is a stability limiting parameter for ADC; the product was voluntarily withdrawn from the US market in 2010 due to safety concerns. 56 InO has an average DAR of 6, and the drug load distribution varies from 0 to 9.…”
Section: Bioconjugation Methods For Adc Linkermentioning
confidence: 99%
“…While it is unclear whether the conjugation of the drug to the N-termini of the mAb directly leads to the formation of aggregates, the structural characterization studies have shown that the level of conjugation to the N-termini of the mAb was higher in aggregates than in the monomeric ADC. 55 …”
Section: Bioconjugation Methods For Adc Linkermentioning
confidence: 99%
See 1 more Smart Citation
“…It is conjugated via an acid cleavable hydrazone linker, 4-(4-acetylphenoxy) butanoic acid (AcBut) to a cytotoxic agent (N-acetyl gamma calicheamicin) [ 21 , 22 ]. It has an average DAR of 2 to 3 [ 23 ]. The linker moiety affixes to exposed lysines (lys) on the antibody.…”
Section: Overview Of Adcsmentioning
confidence: 99%